Sustainability index analysis of traditional organic coffee agroforestry in Pati Regency, Central Java, Indonesia - Afrianto, Whisnu Febry; Tanjungsari, Rahila Junika; Wati, Susanti Indriya; Hidayatullah, Taufiq; Zulkarnaini; Sari, Henny Puspita; Izzudin, Muhammad; Ilham, Muhammad (Ethnobotany Research and Applications, 2024)
Background: Indonesia is one of the countries that contributes the most significantly to the global production of coffee. This study aims to determine organic farming practices and the diversity of plants in coffee agroforestry. Method: This research was carried out in the organic coffee-growing region of Gunungsari Village, Pati Regency, Central Java, Indonesia. Data were collected through field observation and semi-structured interviews containing 47 attributes, such as ecological, economic, social, institutional, and technology dimensions. It was examined utilizing the Multidimensional Scaling (MDS) method using RAPFISH software and Monte Carlo analysis to demonstrate the sustainability status leverage attributes and discuss scoring errors and interpretations. Results: Based on the analysis results of the sustainability status, the traditional organic coffee agroforestry system in Gunungsari Village was fairly sustainable, and the highest value was 74.25 social dimension. The attribute of social dimensions was education level, which had the highest RSM value of 8.62. The Monte Carlo analysis test results showed that the values for all sizes were almost the same as the MDS analysis results. Conclusions: Therefore, increasing farmer education is very important to increase agricultural productivity, introduce technological innovations, and empower them with knowledge and skills that can increase crop yields and economic prosperity in the agricultural sector. Keywords: Gunungsari Village, multi-dimensional scaling, organic coffee agroforestry, RAPFISH, sustainability Abstrak Latar belakang: Indonesia merupakan salah satu negara yang memberikan kontribusi besar terhadap produksi kopi dunia. Penelitian ini bertujuan untuk menganalisis praktik pertanian organik dan keanekaragaman tanaman di wanatani kopi. Penelitian ini dilakukan di daerah penghasil kopi organik di Desa Gunungsari, Kabupaten Pati, Jawa Tengah, Indonesia. Metode: Data dikumpulkan melalui observasi lapangan dan wawancara semi-terstruktur yang terdiri dari 47 atribut, seperti dimensi ekologi, ekonomi, sosial, kelembagaan, dan teknologi. Penelitian ini menggunakan metode Multidimensional Scaling (MDS) dengan menggunakan perangkat lunak RAPFISH dan analisis Monte Carlo untuk menunjukkan atribut pengungkit status keberlanjutan serta membahas kesalahan skoring dan interpretasi. Hasil: Berdasarkan hasil analisis status keberlanjutan, sistem wanatani kopi organik tradisional di Desa Gunungsari tergolong cukup berkelanjutan, dengan nilai tertinggi pada dimensi sosial sebesar 74,25. Atribut dari dimensi sosial yaitu tingkat pendidikan memiliki nilai RSM tertinggi yaitu 8,62. Hasil uji analisis Monte Carlo menunjukkan bahwa nilai untuk semua dimensi hampir sama dengan hasil analisis MDS. Kesimpulan: Oleh karena itu, peningkatan pendidikan petani sangat penting untuk meningkatkan produktivitas pertanian, memperkenalkan inovasi teknologi, dan memberdayakan mereka dengan pengetahuan dan keterampilan yang dapat meningkatkan hasil panen dan kesejahteraan ekonomi di sektor pertanian. Kata kunci: Desa Gunungsari, penskalaan multi-dimensi, wanatani kopi organik, RAPFISH, keberlanjutan